Mathematical modelling of improving the physical and mechanical properties of vehicle movement parameters in mountain conditions (The Peerian Journal, 2024)
The article discusses new scientific approaches to the laws of vehicle movement on a mountain road and their analysis in a new interpretation. The results of scientific research related to improving traffic safety in extreme road conditions are presented. Scientific proposals are given